Revolver. - Revolver; Ahlqvist, Pepe, 1956-; Ahonen, Asko (muusikko); Auer, Petri; Helasvuo, Susanne; Jaatinen, Jussi; Lampinen, Hombre, 1961-2016; Leppänen, Sauli; Nikkinen, Jiri, 1965-; Oinonen, Puka, 1959-; Perelló, Henrik, 1969-; Pohjola, Matti, 1963-2002; et al. (Helsinki : Audiovox Records Oy, 1994)
12 kappaletta.
Revolver (yhtye): Jiri Nikkinen (lauluääni, kitara), Hombre Lampinen (kitara), Asko Ahonen (bassokitara), Harri Seppälä (rummut). Lisäksi: Pekka Pohjola (orkesterin johtaja), Pepe Ahlqvist (huuliharppu), Puka Oinonen (sitar, tampura), Jari Puhakka (kosketinsoittimet), Petri Auer (kosketinsoittimet), Tapio Siitonen (piano), Sauli Leppänen (basso), viulu, puhallinsoittimet: Matti Pohjola, Susanne Helasvuo, Tuula Riisalo, Henrik Perellä, Heljä Räty, Jussi Jaatinen.
Julkaistu myös C-kasettina.
Sanat tekstiliitteessä: suomi.
Luettelointi kesken
Keywords: Revolver -- albumit; rock